Heat mitigation effects of urban parks and gardens on surrounding areas in hot, arid environments: A case study of Shiraz - Mahshad Naeim; Nazanin Nasrollahi; Mohammad Taleghani (Journal of Cleaner Production, 2026)

Volatile oil constituents, antioxidant and antibacterial activities of Lonicera caprifolium L. in different areas of Iran - Mohammad Rahmati; Samira Eghbali; Majid Mokaber-Esfahani; Akram Taleghani (Natural Product Research, 2025)

Unmasking early colorectal cancer clues: in silico and in vitro investigation of downregulated IGF2, SOCS1, MLH1, and CACNA1G in SSA polyps - Seyedeh Nasim Mirbahari; Nayeralsadat Fatemi; Sanaz Savabkar; Vahid Chaleshi; Neda Zali; Mohammad Yaghoob Taleghani; Ebrahim Mirzaei; Leili Rejali; Pardis Ketabi Moghadam; Ehsan Nazemalhosseini Mojarad (Molecular Biology Reports, 2024)
Background and aim Colorectal cancer (CRC) originates from pre-existing polyps in the colon. The development of different subtypes of CRC is influenced by various genetic and epigenetic characteristics. CpG island methylator phenotype (CIMP) is found in about 15–20% of sporadic CRCs and is associated with hypermethylation of certain gene promoters. This study aims to find prognostic genes and compare their expression and methylation status as potential biomarkers in patients with serrated sessile adenomas/polyps (SSAP) and CRC, in order to evaluate which, one is a better predictor of disease. Method This study employed a multi-phase approach to investigate genes associated with CRC and SSAP. Initially, two gene expression datasets were analyzed using R and Limma package to identify differentially expressed genes (DEGs). Venn diagram analysis further refined the selection, revealing four genes from the Weissenberg panel with significant changes. These genes, underwent thorough in silico evaluations. Once confirmed, they proceeded to wet lab experimentation, focusing on expression and methylation status. This comprehensive methodology ensured a robust examination of the genes involved in CRC and SSAP. Result This study identified cancer-specific genes, with 8,351 and 1,769 genes specifically down-regulated in SSAP and CRC tissues, respectively. The down-regulated genes were associated with cell adhesion, negative regulation of cell proliferation, and drug response. Four highly downregulated genes in the Weissenberg panel, including CACNA1G , IGF2 , MLH1 , and SOCS1 . In vitro analysis showed that they are hypermethylated in both SSAP and CRC samples while their expressions decreased only in CRC samples. Conclusion This suggests that the decrease in gene expression could help determine whether a polyp will become cancerous. Using both methylation status and gene expression status of genes in the Weissenberg panel in prognostic tests may lead to better prognoses for patients.

Rural heat island effect of centralized residences in China: Mitigation through localized measures - Yiming Du; Anxiao Zhang; Qi Zhen; Mohammad Taleghani; Chi Zheng; Ling Zhu; Yue Zheng; Qi Zhang (Sustainable Cities and Society, 2024)

The impact of local microclimates and Urban Greening Factor on schools’ thermal conditions during summer: A study in Coventry, UK - Yasaman Namazi; Susanne Charlesworth; Azadeh Montazami; Mohammad Taleghani (Building and Environment, 2024)

Up regulation of long non-coding RNAs BACE1 and down regulation of LINC-PINT are associated with CRC clinicopathological characteristics - Sara Bakhtiari-Nezhad; Leili Rejali; Mahrooyeh Hadizadeh; Mohammad Yaghob Taleghani; Hamid Asadzadeh Aghdaei; Chris Young; Binazir Khanabadi; Ehsan Nazemalhosseini-Mojarad; Maziar Ashrafian Bonab (Molecular Biology Reports, 2022)
Background Long non-coding RNAs (LncRNAs) are known to have regulatory consequences for aberrant gene expression in cancers. The aim of this study was to evaluate the expression levels of long non-encoding RNAs, BACE1 (β-secretase1) and LINC-PINT (Long Intergenic Non-Protein Coding RNA, P53 Induced Transcript), in colorectal cancer (CRC) with clinicopathological parameters. Methods and results Bioinformatics analysis defining effectual signalling pathways Wnt. A total of 130 tissue samples (50 fresh CRC tissues with parallel adjacent normal tissues (ADJ) accompanied with 30 normal healthy control tissue samples) were collected from the Iranian population. mRNA expression analysis was performed via Real Time Q-PCR. Statistical analysis for comparing CRC expression levels with ADJ and normal healthy tissues were carried out using Kruskal–Wallis tests. The Receiver Operating Characteristic (ROC) curve was plotted for each LNC, separately. We discovered that PINT and BACE1 expression levels were decreased and increased respectively in CRC tumour samples compared with ADJ normal and healthy tissues. Clinicopathological parameter assessment revealed a significant relationship between PINT expression, tumour location, staging and distant metastasis (p < 0.009, p < 0.014, p < 0.008, respectively). Also, BACE1 over expression was significantly associated with tumour site (p < 0.009), metastasis (p < 0.017) and histological differentiation (p < 0.028) and staging (p < 0.017). Furthermore, ROC curve plotting showed LINC-PINT LNC-BACE1 may distinguish between early and late-stage of CRC, highlighting the value of both BACE1 and PINT as CRC progression biomarkers. Conclusion We investigated two LNCRNAs (PINT and BACE1) as potential CRC prognostic biomarkers, which are imperative for early and effective medical intervention in CRC. Expression levels of PINT and BACE1 in CRC tissue samples may serve to identify metastasis earlier, increasing patient survival rates and expediating clinical treatment options.

Environmental evaluation and optimization of energy use and greenhouse gases mitigation for farm production systems in Mashhad, Iran - Abolfazl Taleghani; Morteza Almassi; Mohammad Ghahderijani (Environmental Science and Pollution Research, 2020)